1990
DOI: 10.3386/w3301
|View full text |Cite
|
Sign up to set email alerts
|

Patent Statistics as Economic Indicators: A Survey

Abstract: This survey reviews the growing use of patent data in economic analysis. After describing some of the main characteristics of patents and patent data, it focuses on the use of patents as an indicator of technological change. Cross-sectional and time-series studies of the relationship of patents to R&D expenditures are reviewed, as well as scattered estimates of the distribution of patent values and the value of patent rights, the latter being based on recent analyses of European patent renewal data. Time-serie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

48
2,772
4
188

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 2,704 publications
(3,012 citation statements)
references
References 0 publications
48
2,772
4
188
Order By: Relevance
“…Patent Activity Analysis. Researchers have long used patents as a measure and descriptive indicator of inventive activity (18). Patents provide detailed and publicly accessible technical and organizational information for inventions over a long period of time.…”
Section: Methodsmentioning
confidence: 99%
“…Patent Activity Analysis. Researchers have long used patents as a measure and descriptive indicator of inventive activity (18). Patents provide detailed and publicly accessible technical and organizational information for inventions over a long period of time.…”
Section: Methodsmentioning
confidence: 99%
“…Within many economics and technology management disciplines, patent statistics have become well defined and established as a proxy factor for the measure of technological capacity and accepted as (albeit imperfect) statistics for innovation and R&D production in the absence of more robust measures [25][26][27]. Patent application and registration is also a system that companies and institutes use to perfect their technological innovations, and for legal reasons, patent-filing information is systematically registered by national government offices [28].…”
Section: Patent Statistics For Tlementioning
confidence: 99%
“…Much research has shown a positive relationship between patenting and R&D institute or company performance, provided that patent applications are weighted according to their quantity and quality [25,29]. The patent statistics used in this Table 2 summarizes an important set of statistics used to analyze technological strategy.…”
Section: Patent Statistics For Tlementioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, we also present alternative measures of H Rt and H Ct , computed simply as employment divided by population. 25 As in Fisher (2006), the price index of capital investment, P K , corresponds to the price of total investment and is constructed with the equipment de ‡ator and the NIPA (National Income and Product Accounts) de ‡ators for residential and nonresidential structures, consumer durables and government investment. The equipment de ‡ator was constructed by Gordon (1990) for the years up to 1980 and was extended by Cummins and Violante (2002) for the years up until 2000.…”
Section: Other Variables Used In the Analysismentioning
confidence: 99%